2016
DOI: 10.1016/j.brainres.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual GLP-1 and GIP receptor agonist is neuroprotective in the MPTP mouse model of Parkinson′s disease by increasing expression of BNDF

Abstract: The incretins glucagon-like peptide 1 (GLP-1) and glucose dependent insulinotropic polypeptide (GIP) are growth factors with neuroprotective properties. GLP-1 mimetics are on the market as treatments for type 2 diabetes and are well tolerated. Both GLP-1 and GIP mimetics have shown neuroprotective properties in animal models of Parkinson's and Alzheimer's disease. In addition, the GLP-1 mimetic exendin-4 has shown protective effects in a clinical trial in Parkinson's disease (PD) patients. Novel GLP-1/GIP dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 69 publications
3
74
0
Order By: Relevance
“…Reduced oxidative stress, more TH-positive dopaminergic neurons and an increase in BDNF were also demonstrated and this was similar to the effect shown using the incretin analogue DA-JC1 [60,82]. This suggests a possible overlap in the pathway by which metformin and incretins exert a neuroprotective effect.…”
Section: Metforminsupporting
confidence: 75%
See 4 more Smart Citations
“…Reduced oxidative stress, more TH-positive dopaminergic neurons and an increase in BDNF were also demonstrated and this was similar to the effect shown using the incretin analogue DA-JC1 [60,82]. This suggests a possible overlap in the pathway by which metformin and incretins exert a neuroprotective effect.…”
Section: Metforminsupporting
confidence: 75%
“…Ji and colleagues [60] have also demonstrated the protective effects of incretins using a protease resistant GLP-1/GIP analogue (DA-JC1) on MPTP models [60]. They found that TH levels were increased following treatment with DA-JC1…”
Section: The Role Of Gip Glp-1 and Dpp4mentioning
confidence: 99%
See 3 more Smart Citations